1998
DOI: 10.1002/(sici)1097-0134(19980501)31:2<160::aid-prot6>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of solution and crystal structures of maize nonspecific lipid transfer protein: A model for a potential in vivo lipid carrier protein

Abstract: The three-dimensional solution structure of maize nonspecific lipid transfer protein (nsLTP) obtained by nuclear magnetic resonance (NMR) is compared to the X-ray structure. Although both structures are very similar, some local structural differences are observed in the first and the fourth helices and in several side-chain conformations. These discrepancies arise partly from intermolecular contacts in the crystal lattice. The main characteristic of nsLTP structures is the presence of an internal hydrophobic c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 52 publications
1
28
0
Order By: Relevance
“…A thorough analysis of the dimensions of the protein cavity showed that the volume is highly variable depending on small conformational changes of internal side-chains and backbone [21]. The present study shows that ns-LTPs are able to interact with both monoacyl and diacyl lipids and with both lipid forming micelles or lamellar liquid-crystalline phases.…”
Section: Resultsmentioning
confidence: 61%
See 2 more Smart Citations
“…A thorough analysis of the dimensions of the protein cavity showed that the volume is highly variable depending on small conformational changes of internal side-chains and backbone [21]. The present study shows that ns-LTPs are able to interact with both monoacyl and diacyl lipids and with both lipid forming micelles or lamellar liquid-crystalline phases.…”
Section: Resultsmentioning
confidence: 61%
“…The volume of the internal hydrophobic cavity occupied by the two myristoyl chains was estimated to be 750 A 3 (±250 A 3 ) using the program 'CAVITE' [21]. The pocket was bordered by hydrophobic residues belonging to the four helices and to the C-terminal tail.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In previous studies of the maize LTP-long chain lipid complex, a hydrogen bond was found between the carboxylate or carbonyl group of the lipid and the hydroxyl of the C-terminal Tyr 81 (in maize LTP numbering), stabilizing the protein-lipid complex (11,12,58). The conserved N-terminal Tyr 17 (in maize LTP numbering) on the helix H1 is mostly solvent-exposed (12), and its role in the lipid complexation is obscure.…”
Section: Slvnpslglnaaivagipakmentioning
confidence: 99%
“…Three-dimensional structures of LTPs from maize (Gomar et al 1996(Gomar et al , 1998, wheat (Pons et al 2003) and barley (Lerche and Poulsen 1998) have led to a model structure of four helices linked by three loops and a C-terminal tail without a regular structure (Han et al 2001;Stolowich et al 1997). A fold is established by the four disulfide bonds and the helices encode an internal K.…”
Section: Introductionmentioning
confidence: 99%